Anxiety mediated the relationship between bullying victimization and internet addiction in adolescents, and family support moderated the relationship - Yang Liu; Jinyin Peng; Jinna Ding; Jing Wang; Chunyan Jin; Lei Xu; Tiancheng Zhang; Pingfan Liu (BMC Pediatrics)
Abstract Objective This study aims to discuss anxiety in mediating role between bullying victimization and adolescent internet addiction, and the moderating role of family support between bullying victimization and adolescent anxiety. Methods A cross-sectional study was conducted in 5 provinces of China by convenience sampling from February to March 2024. A total of 1395 participants (599 boys and 796 girls) with an average age of 15.86 ± 0.74 years were included in the final analysis. Subjective data on bullying victimization, internet addiction, anxiety, and family support were collected and analyzed. A moderated mediation model was constructed. Results After controlling for age and gender, bullying victimization was found to be a significant predictor of internet addiction (β = 0.130, p < 0.001). Anxiety has a complete mediating effect between bullying victimization and adolescent internet addiction. Specifically, bullying victimization significantly predicted adolescent anxiety (β = 0.264, p < 0.001). anxiety significantly predicted adolescent internet addiction (β = 0.417, p < 0.001). Family support alleviated the relationship between bullying victimization and anxiety (β= -0.032, p < 0.05). Conclusions Bullying victimization can predict internet addiction through anxiety in adolescents, and family support can alleviate the predictive relationship between bullying victimization and adolescent anxiety. It is suggested that guardians should provide adequate support to adolescent bullying victimization in order to reduce the negative impact of bullying victimization on adolescents and prevent the occurrence of internet addiction.